Proprium hominis : la persona y su vida moral en los comentarios bíblicos de Tomás de Aquino - Roszak, Piot (Sapientia, 2017)
The paper starts with the sentence from the sermo Homo quidam: «What is proper to man? Being mild in nature (…) So, because of our similarity and intimacy with God and his property, anyone ought to be uncorrupted, devoted to God and kind to his neighbor» and I will try to analyze the virtues of mansuetudo and benignitas in biblical commentary of Aquinas (but also ethical consequences of Deo devotus). There will be a place for some general remarks about Aquinas virtue ethic.